Cardiovascular outcomes of patients with type 2 diabetes after myocardial infarction and the impact of diabetes duration: a nationwide registry study - Kerola, Anne M.; Juonala, Markus; Kytö, Ville (ELSEVIER IRELAND LTD, 2026)
Aims: To study long-term cardiovascular outcomes following a myocardial infarction (MI) among patients with type 2 diabetes.
Methods: Patients surviving 90 days after MI with type 2 diabetes (n = 10,440) or without diabetes (n = 65,315) during 2004-2018 were identified from Finnish nationwide registries. The primary outcome, a major adverse cardiovascular event (MACE; recurrent MI, ischemic stroke, heart failure hospitalization, or cardiovascular death), was studied using competing risk Fine-Gray analyses. Median (maximum) follow-up was 3.7 (12) years. Differences between groups were balanced by multivariable adjustments and propensity score matching (n = 10,300 patient pairs).
Results: 12-year cumulative incidence of MACE was higher in patients with type 2 diabetes (68.8 %) compared to propensity score-matched patients without diabetes (56.1 %) (sub-distribution hazard ratio [sHR]: 1.36; 95 % CI: 1.31-1.41). Incidences of recurrent MI (sHR 1.49; 95 % CI 1.41-1.57), ischemic stroke (1.14; 1.05-1.23), heart failure hospitalization (1.48; 1.40-1.57), and cardiovascular death (1.30; 1.24-1.36) were higher in patients with type 2 diabetes. Longer diabetes duration was associated with MACE, recurrent MI, heart failure, and cardiovascular death.
Conclusions: Patients with type 2 diabetes have impaired long-term cardiovascular outcomes after an MI, underlining the importance of effective secondary prevention. Patients with a longer diabetes duration are at a particularly high risk.